Clean by light irradiation practical applications of supported TiO2 - Augugliaro, Vincenzo; Loddo, Vittorio; Palmisano, Giovanni; Palmisano, Leonardo; Pagliaro, Mario (Royal Society of Chemistry, 2010)
Covers the environmentally friendly cleaning materials functionalized with TiO2, a widely known semiconductor causing redox reactions under artificial or solar irradiation.